2019
DOI: 10.1029/2019ja027102
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency (f < 200 Hz) Polar Plasmaspheric Hiss: Coherent and Intense

Abstract: Low frequency (LF)~22 Hz to 200 Hz plasmaspheric hiss was studied using a year of Polar plasma wave data occurring during solar cycle minimum. The waves are found to be most intense in the noon and early dusk sectors. When only the most intense LF (ILF) hiss was examined, they are found to be substorm dependent and most prominent in the noon sector. The noon sector ILF waves were also determined to be independent of solar wind ram pressure. The ILF hiss intensity is independent of magnetic latitude. ILF hiss i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 124 publications
(268 reference statements)
1
16
0
Order By: Relevance
“…Overall, the effects of magnetosonic waves on electrons are weakest compared to the other three types of plasma waves. It is noteworthy that we performed test particle simulations to calculate diffusion coefficients for coherent VLF transmitter waves and plasmaspheric hiss 32,35,36 , and found that the test particle simulation results agree well with the quasi-linear calculation results due to the weak wave amplitudes during this relatively quiet event under investigation (see the section of Test particle simulations for coherent plasmaspheric hiss and VLF transmitter waves in the Supplementary Methods and Supplementary Fig. 4).…”
Section: Resultssupporting
confidence: 60%
“…Overall, the effects of magnetosonic waves on electrons are weakest compared to the other three types of plasma waves. It is noteworthy that we performed test particle simulations to calculate diffusion coefficients for coherent VLF transmitter waves and plasmaspheric hiss 32,35,36 , and found that the test particle simulation results agree well with the quasi-linear calculation results due to the weak wave amplitudes during this relatively quiet event under investigation (see the section of Test particle simulations for coherent plasmaspheric hiss and VLF transmitter waves in the Supplementary Methods and Supplementary Fig. 4).…”
Section: Resultssupporting
confidence: 60%
“…Furthermore, the compression of the dayside magnetosphere creates local magnetic field minima away from the equator (Fig. 2.9) where the growth rate of chorus waves increases and from where they have a shorter distance to propagate to the plasmapause, minimizing the Landau damping before entering the plasmasphere (Tsurutani et al 2019).…”
Section: Driving Of Plasmaspheric Hissmentioning
confidence: 99%
“…Zhang et al, 2019). The strong precipitation of relativistic electrons triggered by the coherent or quasi-coherent plasmaspheric hiss and EMIC waves can cause the fast formation of the electron slot region (Falkowski et al, 2017;Tsurutani et al, 2018Tsurutani et al, , 2019 and the dropout of radiation belt relativistic electrons within 1 hour (Remya et al, 2015;Tsurutani et al, 2016). Through Landau resonance, plasmaspheric hiss can heat suprathermal electrons inside the plasmasphere (e.g., Bortnik et al, 2008;Chen et al, 2009;Cornwall et al, 1971;Hasegawa & Mima, 1978;Woodroffe et al, 2017;.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Plasmaspheric hiss is whistler‐mode emission generally at frequencies from 20 Hz to several kHz below 0.5 f ce (equatorial electron cyclotron frequency) (Meredith et al., 2004; Thorne et al., 1973). There are still debates over the two classes of sources proposed for the plasmaspheric hiss: (a) background plasma noises inside the plasmasphere (Omura et al., 2015; Su et al., 2018a; Thorne et al., 1979); (b) other plasma waves outside the plasmasphere (lightning whistlers or chorus waves) (Bortnik et al., 2008, 2009; Chen, Bortnik, et al., 2012; Green et al., 2005; Church & Thorne, 1983; Falkowski et al., 2017; Sonwalkar & Inan, 1989; Tsurutani et al., 2012, 2015, 2018, 2019). EMIC waves are predominantly left‐hand polarized electromagnetic emissions at frequencies below f H (equatorial hydrogen cyclotron frequency) (Erlandson et al., 1992; Perraut, 1982; Remya et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation